Strength Characteristics and Failure Mechanism of Granite with Cross Cracks at Different Angles Based on DIC Method - Xu Wu; Liyuan Zhang; Jinglai Sun; Qifeng Guo; Jiliang Pan; Jun Gao (Advances in Materials Science and Engineering)
The engineering rock mass is generally composed of the rock matrix and structural plane and is an anisotropic inhomogeneous geological body. Accidents such as roof collapse and well caving caused by joint and fissure expansion occur frequently during tunnel excavation and service, resulting in serious casualties and economic losses. It is of great theoretical significance and engineering value to study the fracture mechanism of the jointed rock mass to ensure the stability of the surrounding rock and the safe and efficient utilization of the urban underground space. To investigate the effects of crossed cracks on mechanical properties and failure characteristics of rock, wire cutting equipment is employed to make rock samples with different crossed cracks, and then acoustic emission system and digital image correlation technique are used to study the fracture process of rock samples under uniaxial compression. It has been found that the strength of rock samples with a single crack is generally larger than that of samples with cross cracks, and the strength changed with the angle of the crack in a “V” shape. When the angle of preexisting crack is 60°, the rock strength reaches the lowest. The primary crack has a more obvious influence on rock strength and is the main controlling factor of rock fracture. The initiation stress of rock samples with a single crack changes more significantly with angle. When the angle of the primary crack is 45°, the rock sample is most prone to crack initiation failure, and the crack initiation stress is only 1/4 to 1/2 of the strength. There are two types of cracks: wing and anti-wing, and the tensile cracks are the main ones. It is revealed that the fracture of cracked rock has significant directional characteristics. For the samples with cross cracks, the primary crack is the main control factor of crack initiation, and the secondary crack has a certain guiding effect on the crack.